The effect of timed insemination on pregnancy rates of cows synchronized with pgf2α based on plasma progesterone levels - Abdullah Kaya; Kenan Çoyan; Mehmet Bozkurt Ataman (Eurasian Journal of Veterinary Sciences)
This study was conducted to investigate the effectiveness of oestrus synchronisation with PGF2α and timed-insemination based on plasma progesterone levels in cows. The study was carried out in 34 Brown Swiss cows, aging between 3 and 5 years otd. Blood samples were collected at ten day intervals 3 times without cyclic stage of the cows. In each sampling, the cows with high plasma progesterone levels (20.5 ng / ml) were intramuscularly injected with PGF2α analogue (0.150 mg D- Cloprostenol), and inseminated at 72 and 96 th. hours fixed-time after the injections. Blood samptes were collected to monitore the progesterone levels for pregnancy diagnosis on the day of 21th after inseminations, then rectal examination were conducted to detect the pregnancy on the day of 60 after the inseminations. In the first sampling, high progesterone levels were found in 23 of 34 cows. These cows were synchronized with PGF2α and 16 of 23 cows became pregnant following the fixed-time inseminations. In the second sampling, S of the 11 cows had high progesterone levels and 4 of these S cows with high progesteron levels became pregnant after the synchronization and inseminations. In the 3 th sampling, 3 cows had lower levels than 0.5 ng / ml plasma progesterone. Total of 31 cows were synchronized based on high progesterone levels and 20 (% 66.6) of these cows became pregnant following the inseminations. As a result, synchronization done with PGF2α. in the cows with luteal activity based on plasma progesterone levels and fixed-time inseminations showed satisfactory pregnancy rates. It was also beneficial for the diagnosis of the cows with no luteal activity and elimination of the PGF2α injections to these cows.